Pelletization of seeds of Raphanus sativus L. cv. Redondo Gigante with graphite for germination under water stress conditions - Freitas, Nobel Penteado; Takaki, Massanori [UNESP] (Brazilian Archives of Biology and Technology, 2000)
O efeito do estresse hídrico é dependente da presença de luz em sementes de rabanete. O efeito da peletização com grafite em pó foi analisado. Luz branca e vermelho-extremo são filtradas pelo grafite aumentando parcialmente a tolerância ao estresse hídrico de -0,77MPa em sementes peletizadas. Embora a luz vermelha também iniba a germinação em condições de estresse a peletização não teve efeito. Nós propomos a peletização de sementes de Raphanus saivus L. cv. redondo gigante como uma prática antes do plantio para aumentar a tolerância ao estresse hídrico.

The effect of water stress on germination of radish seeds is dependent on the presence of light. The effect of pelletization of radish seeds with powdered graphite on the tolerance to water stress under light was analysed. White light and far-red lights were filtered by graphite increasing slightly the tolerance of pelleted seeds to water stress of -0.77MPa. Although red light also inhibited seed germination the graphite had no effect. We propose the pelletization of seeds of Raphanus sativus, at least in cv redondo gigante with graphite as a pratice before planting to increase the tolerance to water stress.
Keywords: Pelletization; Raphanus sativus; seed germination; water stress